Correlation properties of thermal orientation fluctuations in nematic liquid crystals with macroscopic inclusions - Vasil'ev, A.N.; Pinkevich, I.P. (Functional Materials, 2005)
Influence of the director interaction with small macroscopic impurity particle surface as well as the cell surface on thermal director fluctuations in the nematic liquid crystal cell has been considered. The interaction with the impurity particle surface has been shown to have a stabilizing effect similar to that of the external field. In the liquid crystal isotropic phase, the interaction mentioned above results in a shift of the nematic phase absolute stability temperature, two existing shift mechanisms may compete with each other.